Penggunaan pendekatan Teaching At The Right Level (TARL) dengan model pembelajaran Problem Based Learning (PBL) sebagai upaya meningkatkan keaktifan dan hasil belajar siswa - Iva Desi Ruliani; Lukman Harun (Pascasarjana Universitas PGRI Semarang, 2024)
This study aims to improve student learning outcomes and engagement through the implementation of the Teaching at the Right Level (TaRL) approach combined with the Problem Based Learning (PBL) model. The TaRL approach focuses on teaching that is appropriate to each student's ability level, while PBL encourages students to actively solve relevant problems, so that it is expected to improve student engagement and learning outcomes. This study was conducted in the form of classroom action research (CAR) consisting of two cycles. Each cycle includes the planning, implementation, observation, and reflection stages. In the first cycle, the results of student learning completion reached 64%. After reflection and improvement in the first cycle, it was continued with the second cycle which showed an increase in student learning completion to 78%. There was a difference in increase of 14% between the first and second cycles. The results of this study indicate that the implementation of the TaRL approach combined with the PBL model can effectively improve student learning outcomes and engagement. The increase in learning completion from the first cycle to the second cycle illustrates that this approach and model are able to accommodate differences in student abilities and facilitate more effective and interesting learning. Thus, the TaRL approach and the PBL model can be used as effective learning strategies to improve the quality of education in the classroom.